Calculation of Energy Levels and Reduced Electric Quadrupole Transition Probability for 22F Isotope Using Oxbash Code - A.K. Hasan; B.A. Zayed (Atom Indonesia, 2020)
A study on the calculation of energy levels and reduced electric quadrupole transition probability for fluorine-22 isotope using Oxbash Code has been carried out. The shell model and OXBASH was used to calculate the energy levels and probability of quadratic transition B(E2) of the 22F isotope in the SD region through PW, CWH active interactions. A comparison was made between the calculation results and the experimental data. The comparison shows considerable consistency with the experimental results. The total angular momentum of the ground level 4+1 was confirmed when comparing with the experimental values. A significant consistency was obtained for the calculated energy values MeV (1.734, 2.387, 2.946) with the available experimental values of the same angular momentum (1+1,12+,4+2). It can be concluded that the reduced transition probabilities B(E2) can be  calculated using the PW, CWH reactions and OXBASH code.